Correction: Refractive changes of a new asymmetric intracorneal ring segment with variable thickness and base width: A 2D finite-element model - García de Oteyza, Gonzalo; Álvarez de Toledo, Juan; Barraquer, Rafael I.; Kling, Sabine (PloS one, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0257222.].